Ameaça do estereótipo em jovens negros na escolha profissional - Santos, Israel Jairo (2018)
This study aimed to verify the influence of the threat of stereotypes on young blacks and whites in the face of professional choice by professions of high and low social status. It is known that stereotypes are shared ideas about a group and serve to maintain the order and status quo of the dominant group (Tajfel, 1981). And the theory of the threat of stereotype makes explicit that the maintenance of the social order is favored to the extent that at the time of an evaluation, if the stereotypes of the group to which the evaluated one belongs belong, and if such stereotypes are related to the evaluation, threat of confirming the negative stereotypy would decrease the subject's performance, confirming the stereotypes about the target group (Steele & Aronson, 1995). In Brazil, stereotypes about the occupation of blacks have been built since slavery, and it is now necessary to understand to what extent the threat to stereotypes can be an explanation for the maintenance of the social order established in this society, blacks occupy the professions of low social status. Thus, in order to achieve this objective, two studies were carried out. Study 1 analyzed the social perception of occupations as to the social status attributed to them and the racial composition of these occupations. A total of 253 adolescents, aged 15-21, participated in high school students from three public schools in Aracaju - Sergipe. The information was collected in a semi structured questionnaire and the data analyzed through the SPSS. Study 2 investigated the influence of the threat to stereotypes on the professional choice of young blacks and whites. From this study, 296 adolescents, aged 15 to 24 years, participated in high school students from three public schools in Aracaju-Sergipe. We sought to replicate the research model of Steele and Aronson (1995), however, in the school context and related to the professional choices of young people regarding the status assigned to them. An almost experimental model was used, in which the threat to the stereotype was manipulated through a text about the reality of the professions by race in Brazil for the "threat group", while the "no threat group" did not go through this procedure. Both groups responded to a semi-structured questionnaire. The results of study 1 indicate that young people, regardless of skin color, perceive racial segregation of the professions; black and white young people attribute higher status professions to whites, and the higher the status attributed to them, the smaller the number of blacks; young black people choose more high status professions than whites. In study 2 it was noticed that young blacks in the stereotype threat tended to choose fewer high status professions compared to non-threatening blacks. Whites did not differ in their choice of high-status professions according to the conditions of threat or no threat to the stereotype. It was concluded from the data that the reality of racial segregation of occupations is still a social barrier to be broken, because the context reinforces social stereotypes about the black; and for black adolescents the threat to stereotypes negatively influences choice by high status professions, corroborating with the maintenance of the status quo of the whitening of professions of high social status.